Analisis Kesalahan Siswa TerkaitKomponen Proses Literasi Matematika PISA di SMPN 4 Kota Bengkulu - Elwan Stiadi; M. Zainudin (IKIP PGRI Bojonegoro, 2023)
Abstract: This study aims to analyze student errors related to the components of the PISA mathematical literacy process. This research is a qualitative descriptive study. In this study, the research subjects were students in grades IX 1 and IX 2 at SMP Negeri 4 Bengkulu City in the odd semester of the 2021/2022 academic year. Data collection techniques used in this study, namely test and interview methods. The components of the PISA mathematical literacy process discussed in this study are Communication, Mathematising, Representation, Reasoning and arguments, Devising strategies for solving problems, Using symbolic, formal and technical language and operations, and Using mathematics tools.. The results showed that there are 40,85% of students make the error of communication processes. There are 48,59% of students make error of mathematising process. There are 53,41% of students make error of representation process. There are 18,6% of students make the error of the process of reasoning and argument. There are 48,69% of students make the error of devising strategies for solving the problems. There are 50,18% of students make the error of using the symbolic, formal and technical language and operations. There are 80,3% of students make the error of using mathematics tools. Keywords : Errors, The process’s components of PISA mathematical literacy Abstrak: Penelitian ini bertujuan untuk menganalisis kesalahan siswa terkait komponen proses literasi matematika PISA. Penelitian ini merupakan penelitian deskriptif kualitatif. Pada penelitian ini yang menjadi subjek penelitian nya adalah siswa kelas IX 1 dan IX 2 SMP Negeri 4 Kota Bengkulu semester ganjil tahun ajaran 2021/2022. Teknik pengumpulan data yang digunakan dalam penelitian ini, taitu metode tes dan wawancara. Komponen proses literasi matematika PISA yang dibahas pada penelitian ini, yaitu Communication, Mathematising, Representation, Reasoning and argument, Devising strategies for solving problem, Using symbolic, formal and technical language and operation, and Using mathematics tools.. Hasil penelitian menunjukkan bahwa sebanyak 40,85% siswa melakukan kesalahan proses communication. Sebanyak 48,59% siswa melakukan kesalahan proses mathematising. Sebanyak 53,41% siswa melakukan kesalahan proses representation. Sebanyak 18,6% siswa melakukan kesalahan proses reasoning and argument. Sebanyak 48,69% siswa melakukan kesalahan proses devising strategies for solving problems. Sebanyak 50,18% siswa melakukan kesalahan proses using symbolic,formal and technical language and operation. Sebanyak 80,3% siswa melakukan kesalahan proses using mathematics tools. Kata kunci : Kesalahan, Komponen Proses Literasi Matematika PISA